Penyebab Berkurangnya Anggota Koperasi: Studi Kasus Koperasi Perkebunan Sawit Perintis - Danuar Musthafa (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2019)
The Koperasi Perkenuban Kelapa Sawit Perintis (KPS Perintis) is a forum for oil palm farmers to improve the quality of their crops. Joining a cooperative should make farmers feel comfortable and get various benefits. Besides that, oil palm farmer cooperatives have a very important role and function as a medium of cooperation, teaching and learning, and increasing the yield of plantation production. However, in recent years, the number of the Perintis KPS members has decreased significantly. By using the Peter M. Blau Social Exchange Theory, this study aims to find the causes of farmers leaving the Peritis Cooperative membership by tracing the experiences of members when they are in groups resulting in social conditions that lead to the departure of members of the Perintis KPS. The method used is a qualitative method with in-depth interviews with research informants who are taken purposively. The results showed that there were five factors that led to the membership withdrawal of KPS Perintis members: First, the imbalance between sanctions and reward received by members. Second, the decline in the quality of Pioneer PPS. Third, the fear of members not being able to pay off bank loans for replanting. Fourth, internal family conflict. Fifth is avoidance of internal family members conflict.